The influence of short-lived halogens on atmospheric chemistry and climate - Saiz-Lopez, Alfonso; Mahajan, Anoop S.; Abbatt, Jonathan; Bobrowski, Nicole; Brown, Steven S.; Burrows, John P.; Carpenter, Lucy J.; Chipperfield, Martyn; Cuevas, Carlos A.; Fernandez, Rafael P.; Hossaini, Ryan; Kinnison, Douglas E.; et al. (Nature, 2025)
Observations have demonstrated the ubiquity of short-lived halogens (SLHs)—defined as organic and inorganic chlorine, bromine and iodine compounds with an overall atmospheric lifetime of less than 6 months—in the global atmosphere. They are primarily emitted naturally from the ocean, cryosphere, volcanoes, salt lakes and the biosphere. However, unregulated anthropogenic sources are increasingly contributing to their atmospheric loading. Some of their natural emissions have increased over time due to anthropogenic pollution, for example, the increased oceanic emissions of iodine compounds due to the deposition of ozone on the sea surface. SLHs affect chemical processes, such as ozone and methane chemistry, and therefore influence air quality and climate. Nevertheless, some of their sources and chemistry are not included in air-quality and climate models used in international assessment reports. Here we describe in detail the various impacts of SLHs on air quality and climate, and make a case for the inclusion of more comprehensive SLH chemistry in future atmospheric, air-quality and climate assessments. In doing so, we also identify gaps in our knowledge of SLH emissions, chemistry, and environmental and climate impacts.